On Afrotropical Mohelia Matile (Diptera, Mycetophilidae): new species and phylogenetic comments - Oliveira, Sarah Siqueira (Zootaxa, 2015)
Mohelia was originally described by Matile for M. nigricauda, from the Comoros. Three new Afrotropical species of Mohelia are described. The male and female terminalia of M. matilei sp.n., M. amorimi sp.n., and M. chandleri sp.n. are illustrated. An additional species, not formally described, is commented on. An identification key is also provided, as well as a distribution map for the genus. The differences between Mohelia and Aphrastomyia Lane & Coher are also discussed.